Physiological and phylogenetic studies of Caloramator and Thermoanaerobacterium species : ethanol and hydrogen production from complex biomass - Margrét Auður Sigurbjörnsdóttir (2009)
Three anerobic, thermophilic bacteria were isolated from hot springs in Graendalur, SW-Iceland. The strains were investigated with respect to phylogenetic, physiology and end product formation. Phylogenetic studies were done with both partial and full 16S rRNA sequence analysis on all three strains. Two of the strains, AK44 and AK35, belong to the genus Caloramator with the closest relation to C. viterbensis. The third strain isolated, AK54, falls within the genus Thermoanaerobacterium with the closest relation to T. acidotolerans. Optimum growth conditions were investigated with respect to temperature and pH. The temperature range for growth varied between the strains; 40.0 – 60.0°C for AK44 and AK35 and 55.0 – 70.0°C for AK54. The pH range varied from 4.0 – 8.0 for strain AK44; pH 6.0 – 8.0 for AK35 and 4.0 – 6.0 for AK54. The ability of utilizing various substrates was tested for all strains. All strains were saccharolytic and degraded mono- and disaccharides. The effect of increased substrate concentration on growth and end product formation was tested. A clear inhibition was observed at increased loadings for all strains. Kinetics of glucose degradation and generation times were investigated under optimal growth conditions. End products from glucose were ethanol, acetate and hydrogen (and CO2) for all strains. The effect of partial pressure of hydrogen on hydrogen production was investigated for strain AK54. The liquid/gas ratio clearly affected the hydrogen capacity of the strain as well as other end products produced. Hydrogen and ethanol production from hydrolysates from various complex biomasses was tested on strain AK54. Different pretreatments were used.